Comments on "Transient Magnetic Shielding of a Planar Conductive Thin Screen via Exact Image Theory" - Stumpf, Martin (IEEE transactions on electromagnetic compatibility, 2024)
The main result of Lovat et al. (2023) is put into context of previously published papers on the subject. Its correction is described.